Business Process Improvement of Outpatient Unit of Type B Private General Hospital in Jakarta - Andreas Sabar (Jurnal Inovasi Global, 2024)
Health is one of the factors in economic development and growth. The higher the quality of health, the greater the potential for economic growth and prosperity over the long term. Some important indicators to illustrate the level of health of a country are health expenditure, infant mortality rate, and life expectancy. The average health expenditure of urban residents is higher than that of rural residents. As one of the components of health expenditure, outpatient treatment was identified as one of the largest constituent components, especially for urban areas such as DKI Jakarta Province. Along with the increasing demand for outpatient services in private public hospitals in Jakarta, there is potential of the increasing end-to-end process service quality problems such as queue length and process bottlenecks. The objectives of this study include evaluating the As-Is outpatient service process, analyzing the effectiveness of the outpatient service process against potential queuing problems, analyzing the root of the problem using a Business Process Management approach that uses Business Process Model and Notation (BPMN) and Value Stream Mapping. The results of the analysis on the To-Be process model show that there is potential for time efficiency in the outpatient service process that can improve overall hospital performance.